PENGARUH KUALITAS PELAYANAN DAN DIRECT MARKETING TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN WARUNG NYOMAN LOVINA - I Kadek Nova Adi Permana; I Wayan Cipta (Jurnal Manajemen Perhotelan dan Pariwisata, 2022)
This study aims to determine the effect of Service Quality and Direct Marketing on purchasing decisions simultaneously and partially at Warung Nyoman Lovina Restaurant. This research is survey research using a questionnaire as an instrument. The sample used is the consumer of Warung Nyoman Lovina Restaurant totaled 125 people using purposive sampling method. Data were collected by questionnaire, and analyzed by multiple linear regression analysis. The results of the study found that: (1) service quality and direct marketing had a significant effect on purchasing decisions. (2) service quality has a positive and significant effect on purchasing decisions. (3) direct marketing has a positive and significant effect on purchasing decisions.